Characteristics of non-urgent visits in emergency department - Baykan, Onur; Meral, Orhan; Ozturk, Tayfun; Gonullu, Hayriye (Annals of Medical Research, 2021)
Aim: In recent years, the number of patients using the emergency department is increasing and majority of these patients constitute non-emergency patients. In this study, it was aimed to examine the green field patients who applied to the emergency department of a tertiary hospital by non-urgent reasons and define the socio-demographic characteristics, the reasons for preferring the emergency department, to assess the rate of urgency defined by the participant, and to contribute to the literature by obtaining data for our country.Materials and Methods: This is a cross-sectional study in which the subjects were selected among the whole green area patients applied to emergency department in between 02 and 11 November 2018. Among these patients, the subjects who did not accept to be included to the study and didn’t fulfill the inclusion criteria were excluded. As a result, a total of 716 patients who accepted to be in the study and fulfilled the inclusion criteria were included to the study. Then, a questionnaire for the aim of assessing the socio-demographic characteristics and the reasons for preferring the emergency department, involving a scale to define the self-report of urgency were applied to those 716 volunteered patients.Results: In our study, 23.9 % of a total of 5644 patients applied to emergency department in between 02 and 11 November 2018 were grouped as non-urgent green area patients by the triage personnel. Of these green area patients those who accepted to be included to the study and fulfilled the inclusion criteria; 356 were female (49.7 %) and 360 were male (50.3 %). When the participants were evaluated according to their level of educations, 5.4 % were illiterate, 4.1 % were literate but had no school graduate, 30.6 % were primary education graduates and 13.4 % were university graduates. According to the reasons for choosing the emergency department, 48.2 % of the patients stated that they applied to the emergency department in need of emergency treatment, 22.5 % of the visitors declared that they were unable to get permission from their work in their working hours and 13.1 % of the visitors applied due to their opinion that things were progressing faster in the emergency department. In addition, the patients were asked to scale their urgency in a 10-point scale and the mean rate of urgency defined by the participants in the self-report scale was found to be 6 points (0-10) and negative correlation was observed between education levels and urgent levels.Conclusion: In this study, we obtained descriptive data about the green field patients who applied to the emergency department by non-urgent reasons, defined their socio-demographic characteristics, revealed the reasons for non-urgent applications to the emergency department, and assessed the self-rate of urgency defined by the participants. Since it can be predicted that the overcrowding generated by these non-urgent visits has negative effects and consequence on patients and employees; we consider that this study and similar studies may be helpful in describing the current problem, may help to solve the problem by contributing to the literature.
Keywords: Adverse outcomes; care quality; emergency department; green tag patients; length of stay; overcrowding; triage